Method for managing fly ash from combustion of petroleum products

By treating petroleum-derived products burning fly ash in a highly acidic environment, vanadium and other heavy metals were successfully recovered, the utilization of effluents and sludge was solved, and the use of chemicals was reduced, achieving efficient resource recycling.

CN119836448AInactive Publication Date: 2025-04-15RE SOLVE SP ZOO
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202380054387.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-18
Filing Date
2023-07-15
Publication Date
2025-04-15
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Prior art In dealing with fly ash derived from combustion of petroleum-derived products, there is a problem of the use of large amounts of effluents and sludge generated after the extraction/leaching process, and the need to use a large number of chemicals to selectively precipitate solution components.

Method used

Water was added to the fly ash from the combustion of the petroleum heavy distillate at a temperature of 15°C to 80°C to form a highly acidic solution with a pH below 2, followed by filtration or centrifugation separation of the resulting solution from the undissolved precipitate, then the vanadium compound was precipitated by adding a strong oxidant, and other metals were precipitated under alkaline conditions, and finally sulfate was precipitated using soluble calcium compound.

Benefits of technology

Almost complete recovery of vanadium and other heavy metals derived from burned fly ash from petroleum-derived products has been achieved, reducing the generation of effluents and no large amounts of chemicals are required, significantly improving the recycling efficiency of resources.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005245824180000101
    Figure BDA0005245824180000101
Patent Text Reader

Abstract

The invention relates to a method for utilizing fly ash derived from the combustion of petroleum-derived products, comprising a step of preparing a filler, in particular for thermoplastic polymers, or a step of recovering metals, in particular vanadium, from fly ash derived from the combustion of heavy fractions of petroleum-derived products. The invention also provides a filter and a composite material comprising a thermoplastic polyolefin polymer according to the filter of the invention.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a method for utilizing fly ash originating from the combustion of petroleum-derived products, the method comprising a step of preparing a filler, in particular a filler for thermoplastic polymers, or a step of recovering metals, in particular vanadium, from fly ash originating from the combustion of heavy fractions of petroleum-derived products. The present invention also provides a filter and a composite material of a thermoplastic polyolefin polymer comprising the filter according to the invention. Technical Field

[0002] The technical field of the invention is the management of fly ash from the combustion of petroleum products. Background Art

[0003] Fly ash is the solid residue from combustion captured in an electrostatic precipitator. Fly ash from the combustion of solid fuels, in particular coal and lignite, is generally known and widely used. Unlike coal ash, fly ash from the combustion of heavy oil fractions (HOFA - heavy oil fly ash), including heavy fuel oil (mazut), has received much less attention and interest. The amount of ash produced is also much smaller than that of coal combustion. Assuming that 1m 3 The fuel oil generates about 2.5 kg of gas with a density of about 0.4 kg / dm 3 Fly ash in the form of extremely light dust, which has unburned carbon as the main component, accounting for 30% to more than 90%, as well as inorganic components such as silicon, iron oxide, aluminosilicates and sulfur, and heavy metals, mainly vanadium and nickel [P.Kwolek, K.Czubajewski, M.Wojnicki, Separation and immobilization of vanadiumfromindustrial fly ash as an insoluble inorganic pigment, Arch.Metall.Mater.65(2020), 2, 901-909, DOI:10.24425 / amm.2020.132837].

[0004] Depending on the source of the oil and the combustion conditions, the vanadium content can range from 2.5% to 30% [Manaa E. SA Selective Leaching of Vanadium from Boiler Oiled Ash Residue Using Sodium Carbonate-Bicarbonate Binary Solution. Chem Technol Ind J. 2018; 13(1): 124].

[0005] Due to the special composition of fly ash under consideration, the main method currently used for the disposal of fly ash is to store it in designated landfills. Only a relatively small proportion is used as a raw material for the extraction of valuable metals (mainly vanadium and nickel) or as an additive for the production of building materials [YS Al-Degs et al. Characterization and utilization of fly ash from heavy fuel oil generated in power stations, Fuel Processing Technology 123 (2014) 41-46, doi.org / 10.1016 / j.fuproc.2014.01.040].

[0006] Generally, vanadium compounds are leached from the ash using either acid or alkali. The precipitate remaining after leaching of the soluble components in acid or alkali, respectively, is generally considered waste. After filtration, the vanadium and other components are extracted from the resulting solution by selective extraction or precipitation using an appropriately selected precipitant.

[0007] Patent specification US 10 406 983 B2 (Vanadium Recovery Process) and publications [e.g., S. Vitolo et al. Recovery of vanadium from a previously burned heavy oil fly ash, Hydrometallurgy 62 (2001). 145-150], known processes are to use fly ash originating from the combustion of heavy fuel oil as raw material, after burning the carbon contained in the ash to obtain vanadium compounds. The patent specification discloses these processes, provided that in a first step the coal in the ash is burned, which leads to a significant reduction in the weight of the ash from which the vanadium is separated, up to 90%, and to a significant increase in its content in the carbon combustion residue.

[0008] Also known are methods involving direct (i.e. without pre-combustion of the carbon contained in the ash) leaching of metal components under acidic or alkaline conditions, followed by selective extraction of vanadium compounds from the resulting solution using various solvents [A. Aburizaiza, Sequential Leaching of Vanadium from Heavy Fuel Oil Fly Ash Generated from Saudi Arabia Thermal Power Plants, Current Journal of Applied Science and Technology, 32(4), 2019, pp. 1-17, doi: 10.9734 / CJAST / 2019 / 46032; R. Navarro et al., Vanadium recovery from oil fly ash by leaching, precipitation and solvent extraction processes, Waste Management 27(2007) 425-438].

[0009] Methods involving direct leaching and extraction of vanadium compounds using various solvents are also known [A. Aburizaiza, Sequential Leaching of Vanadium from Heavy Fuel Oil Fly Ash Generated from Saudi Arabia Thermal Power Plants, Current Journal of Applied Science and Technology, 32(4), 2019, pp. 1-17, doi: 10.9734 / CJAST / 2019 / 46032]. The main limitation of the method involves the problematic utilization of the large amount of effluent and sludge generated after the extraction / leaching process, which is generally considered as waste intended to be stored in landfills.

[0010] The direct leaching of vanadium under alkaline conditions and its selective precipitation from the resulting solution are known, for example, from patent specifications US Pat. No. 4,640,823 and WO 2019 / 193510 A1.

[0011] A process involving leaching of vanadium with acid is known, for example, from patent specification US Pat. No. 10,301,705 B2, in which vanadium compounds are recovered in the form of an electrolyte solution for use in redox flow batteries.

[0012] WO 2004 / 090179 specification discloses a method for recovering vanadium from ash, which involves dissolving vanadium compounds in sulfuric acid at a pH of 1 to 1.5. Once the undissolved precipitate has been filtered out, the resulting solution is treated with Na2SO3 to reduce the vanadium compounds to the tetravalent form. The pH of the solution is then adjusted to 5.2 to 5.5 with NaOH, and the vanadium is precipitated in the form of V2O4.

[0013] Due to its high carbon content, fly ash from the combustion of heavy fuel oil product fractions (HOFA) has been used as an additive in the production of Portland cement and geopolymers [M. Alshaaer et al., Production of Heavy Fuel Oil FlyAsh (HFO)-based Geopolymers for Passive Cooling Systems, International Journal of Applied Engineering Research, vol. 13 (1) 2018, pp. 137-143]. It is also known that the ash is used as a pigment for concrete. Here, the metal impurities in HOFA are fixed in the concrete matrix [Woo-Teck Kwon, Dong-Hyun Kim and Yung-Phil Kim Characterization of Heavy Oil Fly Ash Generated from a Power Plant "Advances in Technology of Materials and Materials Processing", 6 [2] (2004) 260-263. DOI: 10.2240 / azojomo0135].

[0014] It is also known that HOFA is used as a raw material for the preparation of activated carbon [S. Salehin et al. Activated carbon from residual oil fly ash for heavy metals removal from aqueous solution, Desalination and Water Treatment 57 (2016) 278-287, doi: 10.1080 / 19443994.2015.1006824; MA Rabah et al. Preparation of valuable products from cleaned carbon of fuel ash, AIMS Materials Science, 4 (5), 2017, 1186-1201. DOI: 10.3934 / matersci.2017.5.1186].

[0015] The use of fly ash from the combustion of heavy fuel oil as an asphalt additive is also known [Patent Application WO 2012 / 061371 A1, Utilization of heavy oil fly ash to improve asphalt binder and asphalt concrete performance], with the proviso that only ashes containing more than 90% carbon and therefore a small proportion of water-soluble or acid-soluble components are used for this purpose.

[0016] WO 2017 / 182043 specification also discloses composite materials based on a matrix of thermoplastic polymers such as polyvinyl chloride, polyethylene or polypropylene, wherein the filler is ash derived from the combustion of oil shale. However, due to the high content of mineral fractions derived from shale, this type of ash is more similar in nature to ash derived from the combustion of coal.

[0017] The manufacture of thermoplastic polymer composites with mineral fillers, in particular ashes, in powder form is generally known and is currently being used on a large scale. Filling polymer materials with mineral fillers improves the properties of the products, primarily by reducing the adverse effects of thermal, post-reaction or post-crystallization shrinkage of these products during their manufacture using various processing techniques, as well as reducing the price of the plastic products. The principle of closed-loop economy and economic considerations make fly ashes from the combustion of coal and lignite an interesting material. Such ashes are characterized by very high contents of silicon, aluminum, and iron and calcium. In addition, metals such as Cr, Co, Ni, Cu, Zn, Cd, Pb are also present in relatively low amounts [K. Galos, A. Uliasz-Bocheńczyk,,, i fly ash from combustion in Poland”Mineral Resources Economy, vol. 21 2005 no.1, 23 - 42; T. Ratajczak et al.,, Characterization fly ash from combustion of some rocky and brown”,Polish Mineralogical Society - Special Works no.13, 1999].

[0018] The use of this type of fly ash in composite materials is known [D. Czarnecka - Komorowska, M. Szostak, N. fly known as synthetic materials Anal. Chem. 2010, 49, 5, 31 - 32; Patent Application WO2012083972A1 Composite of polymeric material with mineral fillers; Polish Patent Application P. 398503, Method of obtaining a composite mass from thermoplastic synthetic materials and fly ash, as a result of combustion in energy units]. Summary of the Invention

[0019] The essence of the invention is a method for utilizing fly ash originating from the combustion of petroleum-derived products, which method comprises extracting water-soluble or acid-soluble components therefrom using water and / or acid, characterized in that water is added to the fly ash originating from the combustion of heavy petroleum fractions in a ratio of 1:3 to 1:5 and at a temperature of 15°C to 80°C, preferably 20°C to 40°C; it is mixed to produce a highly acidic solution with a pH lower than 2, preferably 0.5 to 1.5, it is possible to add a solution of sulfuric (VI) acid or sulfuric (IV) acid, then the resulting solution is separated from the undissolved precipitate using known methods, preferably by filtration or centrifugation, then the vanadium compounds are precipitated from the purified solution by adding an aqueous solution of a strong oxidizing agent, preferably a 20% to 30% aqueous hydrogen peroxide solution, and the mixture is kept at a temperature of 70°C to 90°C, preferably 80°C to 85°C, for 0.5 to 5 hours, preferably 1 to 2 hours. Now, the other metals forming insoluble hydroxides, in particular nickel, iron and aluminum, are precipitated from this solution by increasing the reaction of the solution remaining after the precipitation of vanadium to 9.0 to 11.0, preferably 10.5, using an alkaline hydroxide, then the precipitate obtained under alkaline conditions is filtered off and the sulfate in the form of calcium sulfate is precipitated from the resulting filtrate using a soluble calcium compound. Now, the precipitate separated from the solution after the extraction of the combustion gases considered in the first step is washed with water until the electrolytic conductivity of the filtrate is less than 1 mS, then the precipitate is dried in solid form.

[0020] In the first step of the process according to the invention, water-soluble and acid-soluble components are leached / extracted. Valuable components, such as vanadium and nickel and sulfates in the form of gypsum, are extracted from the resulting solution in a subsequent step and the residue after leaching / extraction is used as a pigment and / or filler in composites with thermoplastic polymers, such as polyethylene (PE) or polypropylene (PP). The use of fly ash in composite materials of this type is known, but this relates to ashes originating from the combustion of coal or lignite, which contain mainly mineral components [D. Czarnecka-Komorowska, M. Szostak, N. Kujawa, Kompozyty nabazie odpadów poliolefin lotnymi” Ap.Chem.2010,49,5,31-32; patent application WO2012083972A1Composite of polymeric material with mineralfillers; Polish patent application P.398503, Sposób otrzymywania masy tworzywa kompozytowegoz termoplastycznych tworzyw sztucznych i lotnych, w wynikuspalania w jednostkach energetycznych].

[0021] In the process of the invention, fly ash resulting from the combustion of petroleum-derived products, in the form of heavy crude oil fractions, in particular heavy fuel oil, or oil distillation residues (HOFA), wherein the carbon content (loss on ignition) ranges from about 40% to more than 90%, wherein the mineral components are mainly silicon compounds, iron, aluminum, sulfur and heavy metals: mainly vanadium, nickel or molybdenum, wherein the water-soluble and acid-soluble components account for 20% to 60%, is separated by water leaching into a fraction insoluble in water and acid and a solution containing dissolved compounds.

[0022] Heavy metals, mainly vanadium and nickel, as well as sulfate in the form of calcium sulfate, are selectively separated from the solution and the solution remaining after precipitate separation is purified using membranes and nanofiltration. The purified water is returned to the process as wash water, thus virtually eliminating the generation of effluent.

[0023] The essence of the invention is also a method for utilizing fly ashes originating from the combustion of petroleum-derived products, comprising a step of preparing a carbonaceous filler, in particular a filler for thermoplastics, comprising adding water to fly ashes originating from the combustion of heavy fractions of crude oil in a ratio of 1:3 to 1:5 and at a temperature of 15°C to 80°C, preferably 20°C to 40°C, mixing them until a highly acidic solution with a pH of less than 2, preferably 0.5 to 1.5, optionally adding a solution of sulfuric (VI) acid or sulfuric (IV) acid, then separating the resulting solution from the undissolved precipitate using known methods, preferably by filtration or centrifugation. The resulting precipitate is washed with water until the electrolytic conductivity of the filtrate is less than 1 mS, and then the precipitate is dried to a solid form.

[0024] The essence of the invention is a filler in the form of a black powder, especially for thermoplastics, which contains carbon, the black powder comprising spherical porous particles, wherein the grain size is 10 to 120 μm, mainly 30 to 80 μm, containing 50% to 80% carbon, mainly 70% to 75%, the other components are mainly compounds of silicon, iron, aluminum and sulfur, and wherein the specific surface area is greater than 6 m 2 / g to 15m 2 / g, fly ash from the combustion of the heavy oil fraction after separation of acid-soluble metals and sulfur compounds.

[0025] The thermoplastic polyolefin polymer composite comprises the filler used in an amount of 0.5 to 50 wt % based on the polymer matrix.

[0026] The method for utilizing fly ash originating from the combustion of petroleum-derived products comprises a step of recovering metals, especially vanadium, from fly ash originating from the combustion of heavy fractions of petroleum-derived products, comprising adding water to fly ash originating from the combustion of heavy fractions of crude oil in a ratio of 1:3 to 1:5 and at a temperature of 15°C to 80°C, preferably 20°C to 40°C, mixing them until a pH of less than 2, preferably a highly acidic solution of 0.5 to 1.5, optionally adding a solution of sulfuric (VI) acid or sulfuric (IV) acid, then separating the resulting solution from undissolved precipitates using known methods, preferably by filtration or centrifugation. Vanadium compounds are then precipitated from the purified solution by adding an aqueous solution of a strong oxidizing agent, preferably a 20% to 30% aqueous hydrogen peroxide solution, and the mixture is kept at a temperature of 70°C to 90°C, preferably 80°C to 85°C, for 0.5 to 5 hours, preferably 1 to 2 hours.

[0027] Other metals forming insoluble hydroxides, in particular nickel, iron and aluminum, are precipitated from the solution remaining after removal of the vanadium compounds, the pH of the solution being increased to 9.0 to 11.0, preferably 10.5, using alkaline hydroxides. Once the precipitate obtained under alkaline conditions has been filtered off, sulfates in the form of calcium sulfate are precipitated from the resulting filtrate using soluble calcium compounds.

[0028] Preferably, once the calcium sulfate precipitate is removed, the filtrate is purified using membrane and nanofiltration methods to produce pure water and a concentrate in the form of brine that is returned to the process.

[0029] Technical issues

[0030] The main limitations of the described methods include the problematic utilization of the large amounts of effluent and sludge generated after the extraction / leaching process, and the necessity to use large amounts of chemicals to selectively precipitate the solution components.

[0031] Solution to the problem

[0032] Surprisingly, it has been found that fly ash originating from the combustion of heavy crude oil fractions, in particular heavy fuel oil and oil distillation residues, can be almost completely recovered in several processing steps. Furthermore, it has been found that under suitable conditions it is possible to recover almost all of the vanadium and selectively recover other ash components dissolved in water, with little use of additional chemicals and reduced effluent generation.

[0033] Surprisingly, it has been found that fly ash resulting from the combustion of petroleum-derived products, in the form of heavy crude oil fractions, in particular heavy fuel oil, or oil distillation residues, with a loss on ignition ranging from about 40% to more than 90%, and wherein the mineral components are mainly silicon compounds, iron, aluminum, sulfur and heavy metals: mainly vanadium, nickel, molybdenum or zinc, can be used as fillers and pigments in composite materials based on thermoplastic polyolefins, such as polyethylene, polypropylene and their recyclables, after leaching of acid-soluble heavy metal compounds.

[0034] The residue remaining after leaching of water-soluble and acid-soluble compounds is in the form of a free-flowing black powder comprising spherical porous particles with a grain size of approximately 10 μm to 120 μm, predominantly 30 μm to 80 μm, and a specific surface area of ​​at least 6 m 2 / g to 15m 2 / g, mainly comprising more than 70% to 75% carbon, and components such as silicon, iron and aluminum, wherein the electrolytic conductivity of the standard water extract (S:L ratio = 1:10) is lower than 1.0 mS, and the residue can be used as a filler in composite materials based on thermoplastic polyolefins, such as polyethylene, polypropylene or their recyclables.

[0035] According to the present invention, it has been found that composite materials with very good mechanical and processing properties can be obtained using fillers derived from fly ash, which is produced by the combustion of petroleum-derived products, which are heavy petroleum-derived fractions, especially heavy fuel oils, or crude oil distillation residues (HOFA), wherein the loss on ignition ranges from about 40% to more than 90%, contains 50% to 80% of carbon, and wherein the mineral components are mainly compounds of silicon, iron, aluminum, sulfur and heavy metals; after leaching out soluble compounds in a highly acidic environment, mainly vanadium, nickel, molybdenum or zinc.

[0036] Advantageous Effects of the Invention

[0037] The invention allows the recovery and further use of all fly ash components generated in power plants during the combustion of heavy fractions of petroleum-derived products, in particular heavy fuel oil or oil distillation residues.

[0038] Heavy metals from HOFA are leached mainly using water, which forms a highly acidic solution (wherein the pH is less than 1) with sulfur compounds, in particular SO2. Under these conditions, all acid-soluble components are removed by repeated leaching. Elemental analysis shows that the leached residue as a filler of the invention is mainly composed of carbon: more than 70% to 75%, while XRF analysis also shows the presence of silicon, iron and aluminum. Unlike carbon black type fillers, the resulting precipitate has hydrophilic properties.

[0039] Studies have shown that the resulting material has very good properties as an active reinforcing filler in polyolefin composites. It also has very good coloring properties as a black pigment. Even at a content of 1% in the composite, the intensity of the black color is comparable to that of a composite containing 30% filler, whether pure polymer or colored recyclables are used.

[0040] The production of the composite material of polyolefin and filler according to the present invention involves mixing the filler in an amount of 0.5 to 50 wt % relative to the polymer matrix with the polyolefin in a suitable ratio and processing into a finished product using known methods.

[0041] Regardless of the matrix type, the Young's modulus values ​​of the obtained composites increase with increasing filler content, and for polyethylene matrices and PE recyclates, an increase in tensile strength was also found. The composites of the invention, even those with a considerable proportion of fillers up to 50%, are characterized by parameters at least similar to those of the polymer matrix, while Young's modulus and tensile strength increase, even by more than 50%, compared to the unfilled polymer, regardless of the polyolefin matrix used. For all tested composites, a decrease in elongation at break was found, while for isotactic polypropylene with 20% of filler added, an increase in impact strength of notched specimens of almost 30% was found. Example

[0042] The invention is illustrated by the following examples.

[0043] Embodiment 1

[0044] 350ml of deionized water is added to 100g of fresh fly ash from the combustion of heavy crude oil fractions, and stirred vigorously for 3 hours at room temperature. The bulk density of the fly ash is about 0.36kg / dcm3, which shows more than 60% ignition loss and 5% vanadium, 4% nickel and 12% iron content. A considerable proportion of ash (more than 40%) is dissolved, and the pH of the resulting mixture is stabilized at 0.8pH. The mixture is then filtered, and the remaining precipitate is washed, so that the solution of the first filtration and the solution of the washing precipitate are collected separately. After washing, the precipitate can be used as a filler in a composite material with thermoplastic polyolefin material. The acid-soluble compounds are separated in the subsequent steps using the solution from the first filtration (without washing the precipitate with water), and the filtrate from the precipitate washing is used to treat the next batch of raw ash instead of deionized water.

[0045] Example II

[0046] To 100 g of fly ash from the combustion of heavy crude oil fractions, 350 ml of deionized water was added and vigorously stirred at a temperature of about 60° C. for 1 hour. The bulk density of the fly ash was about 0.45 kg / dcm 3, containing about 10% vanadium, 4% nickel, 6% iron, 13% sulfur and small amounts of aluminum, magnesium and zinc. A considerable proportion of the ash (about 60%) dissolved, and the pH of the resulting mixture was stabilized at a pH of about 3.5, which was lowered to pH 1.5 by adding sulfuric (VI) acid or sulfuric (IV) acid solution. The further procedure was the same as in Example I.

[0047] Example III

[0048] To the first filtered solution of the mixture from Example I, containing about 44 g / L of dissolved vanadium, 60 ml of a 20% aqueous hydrogen peroxide solution was added, then heated to a temperature of about 70° C. and kept at this temperature for 2 hours. A brown-black precipitate containing vanadium, in the form of oxides, precipitated, with a small impurity content of less than 2%, mainly iron compounds. The precipitate was the raw material for obtaining pure vanadium compounds and was separated from the solution by filtration.

[0049] Example IV

[0050] The solution from Example II was processed as in Example III: 35 ml of 30% hydrogen peroxide solution were added and heated for 1 hour at a temperature of about 85° C. As in Example III, a brown-black precipitate containing vanadium in the form of oxides and small amounts of impurities precipitated.

[0051] Example V

[0052] After separation of the vanadium compounds, soda lye is added to the filtrate of Example III to obtain a pH of about 10.5, the remaining alkali-insoluble metals, mainly nickel, iron and aluminum, are precipitated, and the resulting mixture is filtered. The filtered precipitate containing a large amount of nickel is the raw material for obtaining nickel compounds, while the filtered solution containing a large amount of sulfate is the raw material for obtaining calcium sulfate (gypsum).

[0053] Example VI

[0054] To the filtered solution of Example IV is added a solution of calcium chloride in an amount sufficient to completely precipitate the sulfate in the form of calcium sulfate. After filtration, the resulting precipitate is the raw material for obtaining gypsum plaster. The resulting filtrate is purified using membrane and nanofiltration methods to produce clean water and brine concentrate that is returned to the process, thus virtually eliminating the generation of effluent.

[0055] Example VII

[0056] The washed precipitate from Example I was dried to a solid material. The resulting free-flowing black powder was subjected to physicochemical analysis and contained spherical porous particles with a grain size of approximately 10 μm to 120 μm, mainly 30 μm to 80 μm, and a specific surface area of ​​6 m2 / g to 15m 2 / g. The electrolytic conductivity of the standard water extract (S:L ratio = 1:10) was below 1.0 mS. Elemental analysis showed that the powder mainly contained more than 70% to 75% carbon, while XRF analysis also showed the presence of silicon, iron and aluminum. The resulting precipitate showed hydrophilic properties.

[0057] Example VIII

[0058] For the precipitate in Example II, the procedure was the same as in Example VII. The product obtained had properties similar to those of the product in Example VII.

[0059] Example IX

[0060] The precipitate of Example I was dried at 80°C for 12 hours and subsequently mixed with polyolefin thermoplastic polymer pellets in various proportions: Tatren HT3 06 polypropylene from Slovnaft, Malen EFABS23-D022 polyethylene from Basell Orlen Polyolefins and recycled polyethylene. The names and properties of the obtained composites are summarized in Table 1.

[0061] Table 1. Characteristics of the analyzed systems

[0062]

[0063] Example X

[0064] The mixture obtained in Example IX was placed in the hopper of an ENGELES 80 / 20HLS injection molding machine and injection molding was carried out under the following conditions: injection speed: 30 mm / s, cooling time: 35 s, filling pressure: 30 MPa, filling time: 7 s, nozzle temperature: 220° C., mold temperature: 35° C. The pellets were used to form dumbbell-shaped moldings according to the PN-68 / C-89034 standard, which were subjected to mechanical tests: static tensile test (according to the PN-EN ISO 527:2012 standard) and Charpy impact test on notched specimens (according to the PN-EN ISO 179-1:2010 standard). The results obtained are summarized in Table 2.

[0065] Table 2. Strength test results.

[0066] sample Young's modulus [MPa] Tensile strength at break[MPa] Elongation at break [%] <![CDATA[Tensile breaking strength [kJ / m 2 > PP 1640 35.6 7.38 4.1 PP_1C 1680 35.5 7.0 3.9 PP_20C 2230 35.5 4.6 5.3 PP_30C 2450 36.1 4.1 3.9 PE 233 8.75 46.7 11.6 PE_30C 499 13.8 18.42 14.1 R 334 10.6 81.8 93.5 R_30C 697 16.3 16.9 63.5

[0067] Furthermore, the water absorption of the resulting composites was tested. Despite the hydrophilic nature of the filler, the increase in water absorption of the resulting composites was minimal: less than 0.5% after 90 days, and therefore not much higher in practice than that of the pure polymer.

[0068] The intensity of the black color of the resulting composites was compared. Even though the filler content of Example III in the composite was 1%, the intensity of the black color was comparable to that of the composite containing 30% filler, whether pure polymer or colored recyclables were used.

[0069] Despite the hydrophilic nature of the filler, the resulting composite showed a minimal increase in water absorption: less than 0.5% after 90 days.

[0070] Industrial Applicability

[0071] The precipitated vanadium oxide is a finished product or can be used as a starting material for obtaining pure vanadium compounds, for example in the form of ammonium salts.

[0072] The undissolved precipitate obtained after the first filtration can be used as filler or pigment in composites with polyolefin thermoplastic polymers (PE, PP).

[0073] The resulting composites are characterized by an intense black color already at a filler content of 1% in the composites, regardless of whether pure polymers or colored recyclates are used.

[0074] Furthermore, DSC studies have shown that the use of composites with fillers obtained from fly ash from the combustion of petroleum-derived products increases the crystallization temperature of the composites by several degrees, which increases the latitude of processing parameters.

Claims

1. A method for utilizing fly ash originating from the combustion of petroleum-derived products, said method comprising a step of preparing a carbonaceous filler, in particular a filler for thermoplastics, characterized in that Water is added to fly ash originating from the combustion of heavy fractions of crude oil in a ratio of 1:3 to 1:5 and at a temperature of 15°C to 80°C, preferably 20°C to 40°C, and mixed until a highly acidic solution with a pH of less than 2, preferably 0.5 to 1.5, optionally adding a solution of sulfuric (VI) acid or sulfuric (IV) acid, and then separating the resulting solution from the undissolved precipitate using known methods, preferably by filtration or centrifugation, and then washing the resulting precipitate with water until the electrolytic conductivity of the filtrate is less than 1 mS, and then drying the precipitate to a solid form.

2. A carbon-containing filler, especially for thermoplastics, characterized in that The carbon-containing filler is a black powder, which comprises spherical porous particles, wherein the grain size is 10 μm to 120 μm, mainly 30 μm to 80 μm, contains 50% to 80% carbon, mainly 70% to 75%, wherein other components are mainly compounds of silicon, iron, aluminum and sulfur, and wherein the specific surface area is greater than 6 m 2 / g to 15m 2 / g, fly ash from the combustion of the heavy oil fraction after separation of acid-soluble metals and sulfur compounds.

3. A thermoplastic polyolefin polymer composite with a filler derived from fly ash, characterized in that The filler according to claim 2 is used in an amount of 0.5 to 50% by weight, based on the polymer matrix.

4. A method for utilizing fly ashes originating from the combustion of petroleum-derived products, said method comprising a step of recovering metals, in particular vanadium, from fly ashes originating from the combustion of heavy fractions of petroleum-derived products, comprising leaching the metals in an acidic environment and selectively precipitating the metals from the solution obtained, characterized in that adding water to said fly ash originating from the combustion of heavy fractions of petroleum in a ratio of 1:3 to 1:5 at a temperature of 15°C to 80°C, preferably 20°C to 40°C; mixing said water and said fly ash to produce a highly acidic solution with a pH below 2, preferably 0.5 to 1.5, possibly adding a solution of sulfuric (VI) acid or sulfuric (IV) acid, subsequently separating the resulting solution from the undissolved precipitate using known methods, preferably by filtration or centrifugation, and subsequently removing the vanadium compound from the purified fly ash by adding an aqueous solution of a strong oxidant, preferably a 20% to 30% aqueous hydrogen peroxide solution The vanadium is precipitated from the solution, the mixture is kept at a temperature of 70° C. to 90° C., preferably 80° C. to 85° C., for 0.5 to 5 hours, preferably 1 to 2 hours, while as an option, the reaction of the solution remaining after the precipitation of the vanadium is increased to 9.0 to 11.0, preferably 10.5, by using an alkaline hydroxide, and other metals that form insoluble hydroxides, in particular nickel, iron and aluminum, are precipitated from the solution, and subsequently, the precipitate obtained under alkaline conditions is filtered out and the sulfate in the form of calcium sulfate is precipitated from the resulting filtrate using a soluble calcium compound.

5. The method according to claim 4, characterized in that Once the calcium sulfate precipitate is removed, the filtrate is purified using membrane and nanofiltration methods to produce pure water and a concentrate in the form of brine that is returned to the process.

Citation Information

Patent Citations

  • Method for producing electrolyte for vanadium batteries from oil sand waste

    US10301705B2

  • Vehicle body structure

    US10406983B1

  • Alkaline leaching of vanadium bearing residues

    US4640823A

  • Method of recovering vanadium oxide flake from diesel oil fly-ash or orimulsion fly-ash

    WO2004090179A1

  • Utilization of heavy oil fly ash to improve asphalt binder and asphalt concrete performance

    WO2012061371A1